Real-time physical deformation and cutting of heterogeneous objects via hybrid coupling of meshless approach and finite element method - Yang, Chen; Li, Shuai; Wang, Lili; Hao, Aimin; Qin, Hong (Computer animation and virtual worlds, 2014)
ABSTRACTThis paper advocates a method for real‐time physical deformation and arbitrary cutting simulation of heterogeneous objects with multi‐material distribution, whose originality centers on the tight coupling of domain‐specific finite element method (FEM) and material distance‐aware meshless approach in a CUDA‐centric parallel simulation framework. We employ hierarchical hexahedron serving as basic building blocks for accurate material‐aware FEM simulation. Meanwhile, local meshless systems are designed to support cross‐FEM‐domain coupling and material‐sensitive propagation while respecting the regularity of finite elements. Directly benefiting from the structural regularity and uniformity of finite elements, our hybrid solution enables the local stiffness matrix pre‐computation and dynamic assembling, adaptive topological updating and precise cutting reconstruction. Moreover, our mathematically‐rigorous solver guarantees unconditional stableness. Experiments demonstrate the superiorities of our system. Copyright © 2014 John Wiley & Sons, Ltd. This paper advocates a novel method for real‐time, large‐scale physical deformation and arbitrary cutting simulation of heterogeneous objects with multi‐material distribution, whose originality centers on the tight coupling of domain‐specific finite element method and material distance‐aware meshless approach in a CUDA‐centric parallel simulation framework.